Efficient energy transfer from Ce3+ to Tb3+ in BaF2: green-emitting phosphors for potential applications in the detection of Cu2+ ions. (5th January 2021) - He, Wenxiang; Du, Hongli; Fu, Juan; Luan, Fangfei; Li, Dewei; Sun, Liyuan; Guo, Dongcai
Abstract : A succession of Ce 3+ and Tb 3+ co-doped BaF2 nanoparticles were synthesized by co-precipitation and hydrothermal methods. Abstract : A succession of Ce 3+ and Tb 3+ co-doped BaF2 nanoparticles were synthesized by co-precipitation and hydrothermal methods. The structure, morphology, elemental composition and photoluminescence characteristics of the doped samples were studied by X-ray diffractometry (XRD), transmission electron microscopy (TEM), X-ray energy spectrometry (EDX), photoluminescence emission spectroscopy (PL) and photoluminescence excitation spectroscopy (PLE). The phosphor has a cubic structure. According to the energy level relationship between Ce 3+ and Tb 3+, the energy transfer mechanism of Ce 3+ and Tb 3+ co-doped BaF2 samples was analyzed. Ce 3+, Tb 3+ co-doped BaF2 shows a strong green emission, and its fluorescence emission intensity is about 9 times higher than that of Tb 3+ single doped BaF2 . The energy transfer efficiency from Ce 3+ to Tb 3+ was calculated using a formula, and it was found that the energy transfer efficiency could reach up to 88.22%. The detection solution was prepared by uniformly dispersing the phosphor in absolute ethanol. Through a comparative study of a series of metal ions, it was found that the detection solution has a peculiar sensitivity to aqueous solutions containing Cu 2+ . At the same time, the relationship between the fluorescence intensity of the detection solution and the concentration of Cu 2+ was studied, and the cause of fluorescence quenching caused by Cu 2+ ions was analyzed from the perspective of energy transfer. From this work, it is considered that the phosphor has a great potential application in the determination of Cu 2+ in practical wastewater.